Navigating the Academic Ecosystem: University Education and Women’s Entrepreneurial Ambitions - Akter, Salina (My University, 2024)
ABSTRACT : This thesis examines the role of university education on the entrepreneurial aspirations of women in Finland, with a particular emphasis on the experiences and perspectives of female students. The research underscores the substantial influence of university environments on the development or suppression of entrepreneurial ambitions among women. Despite Finland’s progressive educational policies, a significant gender disparity persists in the field of entrepreneurship. The objective of this research is to determine the barriers and facilitators within academic institutions that influence the entrepreneurial engagement of female students. The study employs the Theory of Planned Behavior (TPB) and Social Cognitive Theory (SCT) to investigate the interaction of environmental factors, social influences, and individual intentions that influence the entrepreneurial behaviors of women. Qualitative data were collected through in depth interviews with eight female students from the University of Vaasa who had completed at least one entrepreneurship-related course. The students were purposively selected. Thematic analysis was implemented to evaluate their experiences, with an emphasis on the relevance of the curriculum, the support provided by institutions, and the challenges that were gender-specific. Results indicate that entrepreneurial education offers indispensable knowledge and abilities; however, women frequently encounter distinctive obstacles, such as inadequate mentorship, networking opportunities, and gender-specific resources. Participants emphasized the importance of mentorship and practical, hands-on experiences, but they also identified deficiencies in curricula and support systems that are specifically designed to meet the requirements of women. Women’s entrepreneurial endeavors and confidence are additionally restricted by structural barriers, including societal norms and implicit biases within academic environments. The study concludes that universities are instrumental in influencing the entrepreneurial aspirations of women by promoting inclusive environments and addressing gender-specific requirements. Suggestions include the promotion of female representation in entrepreneurial networks, the provision of targeted mentorship and resources, and the updating of curricula to reflect diverse experiences. It is the objective of these insights to inform educational strategies that will enable women to confidently pursue entrepreneurship.
Keywords: entrepreneurship; entrepreneurship education; universities; gender; entrepreneurs; women; students; tertiary education; institutions of higher education; barriers; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development